Recurrent Waves of Jailbreak in Nigeria: The Imperatives of Prison Intelligence and Dynamic Security Strategies in Managing the Nigerian Correctional Facilities - Abiodun, Dr. Temitope Francis; Akinlade, Marcus Temitayo (Advances in Social Sciences Research Journal, 2021)
This paper painstakingly addresses the phenomenon of rising waves of prison or jailbreak in Nigeria. And as generally observed according to the dictates of Nigerian law, jail or prison break remains an illegal or unlawful act under which a prisoner forces his or her way out of the prison in a state. This phenomenon of jailbreaks has in one way or the other impacted negatively on the society and posed dangerous threats to national peace and security. The paper in its objectives endeavours to: highlight the series of jailbreaks that have taken place in Nigeria and the various techniques employed by the escapees; interrogate the causal factors of jailbreaks in the country; and also examine the roles of prison intelligence and dynamic security in curtailing the menace. The study makes use of the regulatory capture theory to explain the bane of the phenomena while descriptive and content-analysis techniques are adopted. With the aid of primary and secondary data, the paper is able to reveal that; corruption, ineffective Correctional Service Arms Squad and Intelligence Unit, lack of prison intelligence and dynamic security, among others have weakened the Nigerian Correctional facilities’ security and led to incessant jailbreaks in Nigeria. The paper, however, recommended; putting in place a very sensitive nature of prison information and intelligence; establishing a prison intelligence management board; adopting a multi-agency approach security strategy; and training of prison-based intelligence officers for intelligence gathering and information sharing as strategies of curtailing the rising spate of jailbreaks in Nigeria.